1960
DOI: 10.1016/0020-708x(60)90015-6
|View full text |Cite
|
Sign up to set email alerts
|

The destruction of Salmonella bacteria in refrigerated liquid whole egg with gamma radiation

Abstract: Thermal pasteurization being a borderline process, it was attempted to use ionizing radiation for rendering whole egg, intended for preservation by other methods than freezing, free from Salmondl~a~. Initial densities of about 107/ml of S. typhirauriura and S. s~nflmberg were used.Irradiation was carried out with a ca. 1500 c Coe°-source, the inoculated whole egg being packed in lacquered tins and kept at ca. 1 °C during this treatment.Six decimal reductions of the Salmonella-species tested were obtained at do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1963
1963
1982
1982

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Particular attention has previously been given to the use of radiation for the elimination of salmonellae from egg products, and a difference was noted in the radiation resistance of different serotypes. In studies on liquid whole egg (Proctor, Joslyn, Nickerson & Lockhart, 1953;Mossel, 1960) and on liquid and frozen egg white ), S. typhi-murium was found to be more resistant than S. senftenberg, and the results presented in this paper show this to be so in a variety of media; in fact, S. typhi-murium was the most consistently resistant serotype examined. Brogle et al (1957) found no such difference in resistance for the two serotypes referred to in whole egg solids, egg yolk solids or frozen egg yolk.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Particular attention has previously been given to the use of radiation for the elimination of salmonellae from egg products, and a difference was noted in the radiation resistance of different serotypes. In studies on liquid whole egg (Proctor, Joslyn, Nickerson & Lockhart, 1953;Mossel, 1960) and on liquid and frozen egg white ), S. typhi-murium was found to be more resistant than S. senftenberg, and the results presented in this paper show this to be so in a variety of media; in fact, S. typhi-murium was the most consistently resistant serotype examined. Brogle et al (1957) found no such difference in resistance for the two serotypes referred to in whole egg solids, egg yolk solids or frozen egg yolk.…”
Section: Discussionmentioning
confidence: 48%
“…Based on D value data only, the dose for egg in the liquid state would also be 0-5 Mrad. but this dose would be expected to have a detrimental effect on quality, such effects being observed at much lower doses by Mossel (1960). At 064 Mrad.…”
Section: Discussionmentioning
confidence: 98%
“…This implies that concentrations of antimicrobial compounds, used in selective media which are of no consequence at all for fully vital cells, limit or even completely inhibit the proliferation of cells of the same organism exposed to any of the listed treatments. It must be admitted that most of the evidence available is that sublethal radiolesions of this sort seem to occur much less frequently and/or are probably considerably less severe than the degree of injury observed secondary to other modes of stressing (Latarjet 1943;Stapleton et al 1953Stapleton et al , 1955Davydoff 1956;Alper et al 1958;Gillies et al 1959;Freeman et al 1960;Mossel 1960Alper 1963;Ley et al 1963; Orce e t Forage e t al. 1964;Adler et al 1966;Cook e t al.…”
Section: Fundamental Aspects Of the Assessment Of "Adequate" Doses Fomentioning
confidence: 99%
“…1972). Such an approach is, obviously, valid only, when the radiation resistance amongst Enterobacteriaceae does not vary significantly with genera; this seems to be the case (Nickerson et al 1957;Mossel 1960;Thornley 1963;Comer et a1. 1963;Mossel e t a1.…”
Section: Estlmation Of Most Probable Effective Dose (Mped) Under Pracmentioning
confidence: 99%
See 1 more Smart Citation